Model Of Green Purchase Intention Environmentally Friendly Packaging In The Micro And Small Business Food Industry In Riau Province - Tengku Firli Musfar; Henni Noviasari; Dian Pratiwi (UNIVED Press, 2024)
In an era of increasing environmental awareness, consumer preferences are changing towards environmentally friendly practices, especially in the food industry. This research aims to develop a comprehensive model of environmentally friendly purchasing intentions by investigating the impact of environmentally friendly packaging on consumer behavior in the micro and small business food industry in Riau Province. The study uses a mixed approach, combining quantitative surveys and qualitative interviews to collect data from consumers and businesses. Quantitative analysis will involve statistical techniques such as regression analysis to identify key factors influencing green purchase intentions. Qualitative data will be analyzed thematically to provide deeper insight into consumer perceptions and business practices regarding environmentally friendly packaging. It is hoped that the findings of this research will contribute to the existing literature on sustainable consumption and provide practical insights for micro and small scale food businesses in Riau Province to improve their environmental sustainability efforts. Ultimately, the developed model will be a valuable tool for policymakers, businesses, and researchers seeking to encourage environmentally responsible practices in the local food industry.